Measuring tourism seasonality across European countries. (October 2018) - Ferrante, Mauro; Lo Magno, Giovanni L.; De Cantis, Stefano
Abstract: This paper will propose a general approach for the analysis and measurement of seasonality in tourism, based on an analysis of the pattern of seasonal swing, as a preliminary step for the assessment of seasonal amplitude. The seasonality of tourism demand across European countries will be analyzed and clusters of countries identified, which are based on a similarity of their seasonal pattern. After discussing the limitations of the most frequently used indices employed in the tourism literature, a new index for measuring seasonality in tourism will be suggested in order to measure seasonal amplitude. The latter takes into account the ordinal and cyclical structures of seasonal variations. The results demonstrate a strong connection between seasonal patterns and the spatial distribution throughout European countries, which may orient future policy actions for dealing with seasonality on a European level. Highlights: A classification of the seasonal patterns in European countries is performed. A new index for seasonal amplitude is implemented. Tourism seasonality differs across European countries. Pattern and amplitude are the two main facets of seasonality. Results may orient counter seasonal policies.